Oil palm independent smallholders’ perception on oil palm residue utilization and willingness to supply oil palm residue in Perak - Low, Ivan Xin-Yi (2019)
The advancement of green technology and strong government policies has sparked the interest to utilize oil palm biomass as a feedstock to various green products. Inclusion of independent smallholders is imperative to prevent jeopardizing the rural community to participate. This study investigates independent smallholders’ perception and their willingness to supply oil palm residues. A total of 270 responses via face-to-face interviews were obtained at oil palm fresh fruit bunch collections centres. Chi-Square and Fisher-Exact analysis was conducted using SPSS version 23. The results indicated that majority of smallholders were aware of oil palm residue-based products and were willing to supply. The main motivational factor was financial economic return. Insufficient resources to harvest and transport oil palm trunk was found as the main barrier to supply residues. This study recommends the formulation of good harvesting system as well as the participation of fresh fruit bunch collection centres as the middleman to facilitate the harvest and collection of oil palm residues. Information from this study is useful to policy makers, financial institutions, and venturing investors to develop effective strategies upon establishing the oil palm residue-based industry.